Research on dynamic mechanical behavior and damage evolution mechanism of Cu/WCp laminated composites - Zhang Yubo; Guo Rongxin; Xia Haiting; Yan Feng; Liu Xing Yao (Materials Research Express, 2021)
In this paper, the effect of WCp particle content (3 and 15 vol.%) and laminate orientation on the mechanical behavior of laminated Cu/WCp/15p and Cu/WCp/3p composites under dynamic impact was investigated using the split Hopkinson pressure bar (SHPB) test. Subsequently, the micro-damage evolution mechanism of the composites was observed by scanning electron microscopy (SEM) and optical microscopy. The results demonstrated that Cu/WCp composites are strain-rate-sensitive, and a significant reinforcing effect of WCp particle content on composite properties was observed. Furthermore, the gradient direction revealed a remarkable effect on the dynamic compressive behavior of functionally gradient materials (FGMs). Microscopic analysis revealed that under the same strain rate, there were no apparent damage characteristics in Cu/WCp/3p, while obvious shear cracks appeared in Cu/WCp/15p. SEM analysis revealed that, in FGM, when the laminate orientation was parallel to the stress wave propagation direction, cracks initiated from one side of Cu/WCp/15p, and then grew through the interface to the other side. A relatively large sliding dislocation was observed at the interlayer interface, and the crack arrested at the Cu/WCp/3p layer. However, although the cracks in FGM also initiated from the side of Cu/WCp/15p, they did not cross the interface, but caused a direct split in the interlayer interface, when the laminate orientation was perpendicular to the stress wave propagation direction.